Efficient and durable oxygen reduction electrocatalyst based on CoMn alloy oxide nanoparticles supported over N-doped porous graphene - Singh, Santosh K.; Kashyap, Varchaswal; Manna, Narugopal; Bhange, Siddheshwar N.; Soni, Roby; Boukherroub, Rabah; Szunerits, Sabine; Kurungot, Sreekurnar (ACS Catalysis, 2017)
Transition metal oxide derived materials are very important for various applications, such as electronics, magnetism, catalysis, electrochemical energy conversion, and storage. Development of efficient and durable catalysts for the oxygen reduction reaction (ORR), an important reaction in fuel cells and metal air batteries, is highly desirable. Moreover, the futuristic catalysts for these applications need to be costeffective in order to ensure a competitive edge for these devices in the energy market. This article describes the synthesis of a cost-effective and efficient electrocatalyst for ORR It is based on supporting CoMn alloy oxide nano particles on N-doped porous graphene through a simple and scalable microwave irradiation method. Microwave irradiation was found to be very crucial for the fast creation of pores in the graphene framework with a concomitant formation of the CoMn alloy oxide nanoparticles. A series of catalysts have been synthesized by varying the Co:Mn ratio, among which, the one with the Co:Mn ratio of 2:1 [designated as CoMn/pNGr(2:1)] displayed remarkably higher ORR activity in 0.1 M KOH solution. It showed a similar to 60 mV potential shift with a low Tafel slope of 74 mV/decade, which is comparable to that derived from the commercial Pt/C catalyst. This high activity of CoMn/pNGr(2:1) has been credited to the cooperative effect arising from the metal entities and the defects present in the N-doped porous graphene. Finally, real system-level validations of the use of CoMn/pNGr(2:1) as cathode catalyst could be performed by fabricating and testing single-cells of an anion-exchange membrane fuel cell (AEMFC) and a primary Zn-air battery, which successfully demonstrated the efficiency of the catalyst to facilitate ORR in real integrated systems of the single-cell assemblies.
Keywords: anion-exchange membrane fuel cell; cooperativity effect; microwave synthesis; oxygen reduction reaction; porous N-doped graphene; Zn-air battery